2019
DOI: 10.15414/jmbfs.2019.9.2.208-215
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Analysis, Antioxidant and Antimicrobial Activities of Three Samples of Dried Figs (Ficus Carica L.) From the Region of Mascara

Abstract: Ficus carica L. have always been known by their power to cure various diseases. This study aims to evaluate the antioxidant activity of twelve different extracts of three samples of dried figs. First, the extracts were tested for their polyphenolic, flavonoid and tannin contents by the Folin–Ciocalteu, the aluminium trichloride and vanillin methods and high-performance liquid chromatography (HPLC) for more characterisation. The antioxidant activity was performed by using thre different methods; the 2,2-diphenyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 51 publications
(52 reference statements)
1
10
0
Order By: Relevance
“…It can be noticed that g peel showed higher DPPH reducing potential compared to the pulp. Similar results have been reported by Benmaghnia et al [32], from dried gs extracts using 4 types of solvents (50% acetone, 70% ethanol, 80% methanol, and water). The ethanolic extract showed the highest DPPH reducing activity (65.1-88.1%), followed by methanolic extract (78.6-84.6%), acetonic extract (78.2-81.3%), and aqueous extract (73.1-80.6%).…”
Section: Antioxidant Of Extractsupporting
confidence: 90%
See 1 more Smart Citation
“…It can be noticed that g peel showed higher DPPH reducing potential compared to the pulp. Similar results have been reported by Benmaghnia et al [32], from dried gs extracts using 4 types of solvents (50% acetone, 70% ethanol, 80% methanol, and water). The ethanolic extract showed the highest DPPH reducing activity (65.1-88.1%), followed by methanolic extract (78.6-84.6%), acetonic extract (78.2-81.3%), and aqueous extract (73.1-80.6%).…”
Section: Antioxidant Of Extractsupporting
confidence: 90%
“…The results revealed that high temperature (80°C) and solvent with higher ethanol concentration (80%) were more effective to extract TFC (2.5 mg/g) compared to 50% ethanol (0.44 mg/g), and lower temperature (25°C). Benmaghnia et al [32] compared four solvents (50% acetone, 70% ethanol, 80% methanol, and water) to evaluate their e ciency to extract phytochemicals from dried gs. Acetone was most e cient to extract TFC (228.22 mg/100g) compared to methanolic extract (38.8 mg/100g).…”
Section: Total Avonoid Contentsmentioning
confidence: 99%
“…Ficus carica dried fruit was selected due to its antioxidant properties and possession of high content of flavonoids. 20 Moreover, due to high content of flavonoids and the ability to inhibit…”
Section: Discussionmentioning
confidence: 99%
“…This diameter was 11 mm in K. pneumoniae, 10 mm in E. coli, and 15 mm in S. typhimurium. A study entitled "Phytochemical analysis, antioxidants and antimicrobial activity of three samples of dried F. carica from the region of Mascara (Western Algeria)" was conducted by Benmaghnia et al (12). The results indicated that ethanol extract could inhibit growth of most strains, and the inhibition zone diameter was 10 mm in S. aureus, 0.8 mm in P. aeruginosa, 10 mm in E. coli, and 10 mm in P. mirabilis.…”
Section: Discussionmentioning
confidence: 99%